Continuous Theta Burst Stimulation of the Posterior Medial Frontal Cortex to Experimentally Reduce Ideological Threat Responses - Holbrook, Colin (J Vis Exp, 2018)
Decades of behavioral science research have documented functional shifts in attitudes and ideological adherence in response to various challenges, but little work to date has illuminated the neural mechanisms underlying these dynamics. This paper describes how continuous theta burst transcranial magnetic stimulation may be employed to experimentally assess the causal contribution of cortical regions to threat-related ideological shifts. In the example protocol provided here, participants are exposed to a threat prime-an explicit reminder of their own inevitable death and bodily decomposition-following a downregulation of the posterior medial frontal cortex (pMFC) or a sham stimulation. Next, disguised within a series of distracter tasks, participants' relative degree of ideological adherence is assessed-in the present example, with regard to coalitional prejudice and religious belief. Participants for whom the pMFC has been downregulated exhibit less coalitionally biased responses to an immigrant critical of the participants' national in-group, and less conviction in positive afterlife beliefs (i.e., God, angels, and heaven), despite having recently been reminded of death. These results complement prior findings that continuous theta burst stimulation of the pMFC influences social conformity and sharing and illustrate the feasibility of investigating the neural basis of high-level social cognitive shifts using transcranial magnetic stimulation.